Value of Efficiency and Worship in Islamic Bank XYZ - Acep Riana Jayaprawira; Roikhan Mochamad Aziz; Dita Nur Amanda (Budapest International Research and Critics University, 2022)
This study aims to analyze Islamic Bank XYZ efficiency level with the DEA method and Islamic Values for the period 2015 to 2019 and to see the effect of input and output variables on Islamic Bank XYZ growth rate. Measuring the degree of efficiency in this study uses the DEA method and Islamic Values with an input variable consisting of the right of a third party to profit-sharing, operating expenses and a variable of operating revenue production. This study is desk research with references from journal, book, and internet media. Methodology uses quantitative comparative with method of Development Envelope Analysis (DEA). The results of this research show that Islamic Bank XYZ efficiency in 2018 and 2019 has an efficiency level of 100 percent, while in 2015, 2016, and 2017 there were inefficiencies of less than 100 percent. The output variable has a good production value effectively producing output, and has a good contribution to Islamic Bank XYZ development compared to the input variable, so the efficiency value has fluctuations in each period. The weighting applied to Islamic Bank XYZ was achieved in the calculation of the reflexivity value with high percentages.